2017
DOI: 10.2147/ott.s123494
|View full text |Cite
|
Sign up to set email alerts
|

High expression of glucose-regulated protein 78 (GRP78) is associated with metastasis and poor prognosis in patients with esophageal squamous cell carcinoma

Abstract: BackgroundGlucose-regulated protein 78 (GRP78) plays an important role in the invasion and metastasis of many human cancers. However, the role of this protein in the progression of invasion and metastasis in esophageal squamous cell carcinoma (ESCC) remains elusive.Patients and methodsImmunohistochemistry and Western blot were performed to analyze GRP78 expression in 92 patients with primary ESCC. The correlation of GRP78 expression with clinicopathological factors was analyzed. In vitro, the expression levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Raiter et al [ 42 ] demonstrated that anti-GRP78 titer in patients with colorectal polyp or cancer was higher than that in healthy subjects. Consistent with the data about esophageal cancer, medullary thyroid carcinoma, pancreatic ductal adenocarcinoma, colorectal cancer, renal clear cell carcinoma, astrocytoma, prostate cancer, lung cancer and hepatocellular carcinoma [ 35 , 43 50 ], we found up-regulated GRP78 expression in gastric cancer, compared with gastric mucosa at both mRNA and protein levels, suggesting that GRP78 hyperexpression was positively linked to gastric carcinogenesis. Although anti-GRP78 antibodies come from 6 companies, and different statistical methods are employed, GRP78 expression and its correlation with clinicopathological parameters are comparatively consistent, indicating that these antibodies mainly recognizes GRP78 protein and its expression trend is not determined by statistics.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Raiter et al [ 42 ] demonstrated that anti-GRP78 titer in patients with colorectal polyp or cancer was higher than that in healthy subjects. Consistent with the data about esophageal cancer, medullary thyroid carcinoma, pancreatic ductal adenocarcinoma, colorectal cancer, renal clear cell carcinoma, astrocytoma, prostate cancer, lung cancer and hepatocellular carcinoma [ 35 , 43 50 ], we found up-regulated GRP78 expression in gastric cancer, compared with gastric mucosa at both mRNA and protein levels, suggesting that GRP78 hyperexpression was positively linked to gastric carcinogenesis. Although anti-GRP78 antibodies come from 6 companies, and different statistical methods are employed, GRP78 expression and its correlation with clinicopathological parameters are comparatively consistent, indicating that these antibodies mainly recognizes GRP78 protein and its expression trend is not determined by statistics.…”
Section: Discussionsupporting
confidence: 91%
“…Reportedly, GRP78 expression was positively related to the poor prognosis of the patients with pancreatic and rectal cancers [ 35 , 51 ]. It might be also demonstrated to indicate the worse prognosis of esophageal cancer, melanoma, advanced laryngeal squamous cell carcinoma, tongue cancer, and glioblastoma as an independent factor [ 43 , 47 , 52 54 ]. Ma et al [ 55 ] reported that the overall survival of patients with high serum GRP78 level was significantly poorer than those with low GRP78 level.…”
Section: Discussionmentioning
confidence: 99%
“…GRP78 overexpression in cancers in comparison with normal possibly demonstrating that the cancer cells were suffer of ER stress which triggered UPR to reestablish the homeostasis of ER and because of the point that cancerous cells form abundant distorted proteins which need GRP78 to form combination with (21,22) . The reduced Grp78 significantly decrease cell growth, migration, and invasion, proposing that this protein have oncogenic utilities (14,23,24) .…”
Section: Discussionmentioning
confidence: 98%
“…The overexpression of UPR sensors has been reported in a large number of human cancers including that of breast, brain, gastrointestinal tract, liver, kidney, pancreas, lung, and prostate . In addition, elevated level of the main UPR regulator GRP78 is often found in tumor tissues and is associated with metastasis, poor prognosis, and resistance to treatment . The UPR involvement in cancer initiation and cell transformation is particularly well documented in gastrointestinal and blood cancers (reviewed in ).…”
Section: The Upr Is An Adaptive Mechanism In Cancer Cellsmentioning
confidence: 99%